Frogs and Toads in Your Pocket : A Guide to Amphibians of the Upper Midwest - Collins, Suzanne L.; VanDeWalle, Terry (Bur Oak guide., 2011)
Informs both amateur and professional herpetologists about all sixteen species of frogs and eight species of toads to be found in the Upper Midwest states of Minnesota, Wisconsin, Illinois, Indiana, Michigan, Ohio, South Dakota, North Dakota, Kansas, Nebraska, Iowa, and Missouri.